Gender role stereotypes in elementary school textbooks - Lamug, Corazon B. (EDUKASYON, 1995)
"The stories and pictures in elementary school textbooks were content analyzed to determine male and female role stereotypes. Reading and Language textbooks in both English and Filipino were analyzed using the categories of family, occupation and activity.